Efficacy of Cold Knife Urethrotomy combined with injection of Triamcinolone in management of Anterior Urethral Strictures - الأمين, اسماعيل; يوسف, محمد; حرفوش , أيمن (Latakia University Journal -Medical Sciences Series, 2022)
Objective: To evaluate Efficacy of Cold Knife Urethrotomy combined with injection of Triamcinolone in management of Anterior Urethral Strictures Methods: 40 Patients were classifed according to the type of stricture, primary and recurrent, and the location and length of the stricture. They were subjected to a cold knife urethrotomy with triamcinolone acetonide injected into the stricture area at a total dose of 40 mg. They were also followed up periodically after 6, 9 and 12 months after this procedure to assess recurrence. . Results: 40 patients with an average age of 31 years and a range of 18-57 years. The follow-up after the first urethrotomy was performed at 6,9,12 months. The success rate for patients with stricture less than 1 cm was 100% during the follow-up period. Under 39 years of age, the success rate during follow-up increased from 64% to 100% with decreasing age Conclusions: The combined injection procedure with cold knife urethrotomy has been Shawn to be safe, easy and effective in decreasing the rate of recurrence and increasing the duration of recurrence.